رۆڵی ماتریاڵ لە هونەری پەیکەرسازی مۆدیرنە بۆ هونەری هاوچەرخ (توێژینەوەی هەڵێنجراو) - طاهر, ئازاد جەمال; حەمەخان, شیروان عەلی (Sulaimani Journal for Humanities, 2023)
Abstract: The progressive history of using materials in western sculptural art witnesses a foundational transformation in the twentieth century. If materials used in sculptural art were limited to stone, bronze, wood and gypsum, the 60s of twentieth century sculptural art opened doors to include in its creation the industrial and synthetic materials, human body, abstract thought, and social processes. This transformation of the use of materials affected the process of production of contemporary sculptural art and fine arts in general. In this study, we discuss the relation of using material to the development of fine arts in the twentieth century and especially in sculpture and object arts and how this relation influenced overhauling innovative thinking and self-reinvention.